Identifikasi bakteri patogen pada jajanan telur gulung yang dijual di Kecamatan Syiah Kuala Banda Aceh - Erlinawati Erlinawati; Safridha Kemala Putri (Politeknik Kesehatan Kemenkes Aceh, 2022)
Background: Pathogenic bacteria can be a significant cause of food poisoning. Bacterial growth in food can also cause undesirable physical or chemical changes, making the food unfit for consumption. Egg roll is a snack easily found in Banda Aceh City, which children and adults generally consume. Snacks that contain high bacteria are very dangerous for health.Objectives: This study aims to determine the types of pathogenic bacteria in egg rolls sold in Syiah Kuala District, Banda Aceh.Methods: This experimental study was conducted in Syiah Kuala District, Banda Aceh City, 2020. Five samples were taken for bacterial examination at the Microbiology Laboratory, Medical Technology Poltekkes Kemenkes Aceh. Bacterial identification on egg rolls was observed for four days. Data analysis was only done descriptively.Results: The study identifying pathogenic bacteria on egg rolls showed that the egg roll samples were contaminated with several harmful bacteria. The bacterial colonies varied from the lowest distribution of 453,333 to the highest of 1,150,000. The bacteria were Citrobacter freundii, Proteus mirabilis, and pathogenic bacteria Salmonella sp.Conclusion: Egg rolls sold on the roadside have been contaminated with bacteria. The bacteria identified were Citrobacter freundii, Proteus mirabilis, and pathogenic bacteria Salmonella sp. Suggestions and efforts are needed from the authorities to conduct health promotion and training for egg roll sellers to maintain hygiene and sanitation of both tools and places of sale.